Ephesians, Colossians, Philemon - Patzia, Arthur G. (Peabody, MA Hendrickson, 1990)
Includes bibliographical references and indexes
Keywords: Bible. N.T. Ephesians -- commentaries; Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries